1997
DOI: 10.1172/jci119818
|View full text |Cite
|
Sign up to set email alerts
|

Leptin rapidly suppresses insulin release from insulinoma cells, rat and human islets and, in vivo, in mice.

Abstract: Obesity is associated with diabetes, and leptin is known to be elevated in obesity. To investigate whether leptin has a direct effect on insulin secretion, isolated rat and human islets and cultured insulinoma cells were studied. In all cases, mouse leptin inhibited insulin secretion at concentrations within the plasma range reported in humans. Insulin mRNA expression was also suppressed in the cultured cells and rat islets. The long form of the leptin receptor (OB-Rb) mRNA was present in the islets and insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
217
1
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(233 citation statements)
references
References 55 publications
10
217
1
5
Order By: Relevance
“…Previous studies have shown leptin to decrease basal insulin secretion from the pancreatic islets 34 and down-regulates insulin gene transcription. 35 Leptin receptors have been demonstrated on the β-pancreatic cell, 36 and in animal studies acute physiologic increases in leptin significantly inhibited glucose stimulated insulin secretion in a dose-dependent manner.…”
Section: Neuropeptides and Impaired Glucose Tolerancementioning
confidence: 92%
“…Previous studies have shown leptin to decrease basal insulin secretion from the pancreatic islets 34 and down-regulates insulin gene transcription. 35 Leptin receptors have been demonstrated on the β-pancreatic cell, 36 and in animal studies acute physiologic increases in leptin significantly inhibited glucose stimulated insulin secretion in a dose-dependent manner.…”
Section: Neuropeptides and Impaired Glucose Tolerancementioning
confidence: 92%
“…In normal fed mice a decrease in plasma insulin and associated rise in glucose were observed after leptin administration (159,160), while infusion of leptin to fasted rats reduced both glucose and insulin (161). This seems to be due to effects on insulin action as well as on insulin release.…”
Section: Effect Of Leptin On Insulin Secretionmentioning
confidence: 94%
“…Suppression of insulin secretion and gene transcription by leptin in the obese range has also been demonstrated in human pancreatic islets. 15,17 It should be noted, however, that not all studies have reported inhibitory effects of leptin on insulin secretion. Thus, Shimizu et al, 24 and Tanizawa et al, 25 have actually shown stimulation of insulin secretion by leptin at a physiological range of concentrations, in HIT-T15 and MIN-6 cells, respectively.…”
Section: Inhibition Of Insulin Transcription By Tnfa and Leptinmentioning
confidence: 99%